2019
DOI: 10.2147/cmar.s167348
|View full text |Cite
|
Sign up to set email alerts
|

<p>Novel variants of unknown significance in the <em>PMS2</em> gene identified in patients with hereditary colon cancer</p>

Abstract: Background: Lynch syndrome is associated with genetic variants in mismatch repair ( MMR ) genes. Pathogenic variants in the MLH1 and MSH2 genes occur in most families in which the phenotype is highly penetrant. These testing criteria are likely to miss individuals with Lynch syndrome due to the less penetrant MMR genes, such as MSH6, MLH3, MSH3, and PMS2 . So far,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…29 A recent study demonstrated that PMS2 gene could manifest LS phenotype in other ways. 30 In addition, our study reported similar numbers of absent MLH1/PMS2 and MSH2/MSH6 proteins, and it may be associated with protein heterodimers, MSH2 dimerizes with MSH6 and MLH1 dimerizes with PMS2 form the functional complex Escherichia coli MutS homologs α (MutSα) and E.coli MutL homologs α (MutLα), respectively. 31 We were surprised to find that the combined deficiency of MSH2 and MSH6 proteins was higher than MSH6 protein alone.…”
Section: Discussionsupporting
confidence: 57%
“…29 A recent study demonstrated that PMS2 gene could manifest LS phenotype in other ways. 30 In addition, our study reported similar numbers of absent MLH1/PMS2 and MSH2/MSH6 proteins, and it may be associated with protein heterodimers, MSH2 dimerizes with MSH6 and MLH1 dimerizes with PMS2 form the functional complex Escherichia coli MutS homologs α (MutSα) and E.coli MutL homologs α (MutLα), respectively. 31 We were surprised to find that the combined deficiency of MSH2 and MSH6 proteins was higher than MSH6 protein alone.…”
Section: Discussionsupporting
confidence: 57%
“…Recent studies have associated mutS homolog 3 (Msh3) variants, which play key roles in mismatch repair alongside other genes, with Lynch syndrome [45]. Our protein studies in GASH/Sal hamsters showed that the ability of the Msh3 variant to bind and therefore repair DNA may be considerably impaired, and hence the increase in Msh3 expression may be a cellular mechanism of compensation for its functional loss.…”
Section: Discussionmentioning
confidence: 85%
“…This variant was identified in three affected patients with LS-related cancer. Point variants in other MMR genes (MLH1, MSH6, PMS2, MLH3, and MSH3) [8][9][10]20], and large rearrangements in these genes (MLH1, MSH2, MSH6, and PMS2) [11,12,21] were not identified in these patients. MSI analysis revealed instability in two dinucleotide repeats, D5S346 and D18S58 (of which only one repeat is of the Bethesda panel), and then a MSI-Low status.…”
Section: Discussionmentioning
confidence: 81%
“…LS is an autosomal dominant condition caused by a defect in one of the MMR genes and is characterized by a high lifetime risk of tumor development, especially colorectal cancer (20-70%), endometrial cancer (15-70%), and other extracolonic tumors (15%) [7]. The molecular characterization of LS patients relies on the identification of point mutations and large rearrangements in the coding regions of the MMR genes, MLH1, MSH2, PMS2, and MSH6 [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%